If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8h + -4g + 5g + 2h = 0 Reorder the terms: -4g + 5g + 8h + 2h = 0 Combine like terms: -4g + 5g = 1g 1g + 8h + 2h = 0 Combine like terms: 8h + 2h = 10h 1g + 10h = 0 Solving 1g + 10h = 0 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-10h' to each side of the equation. 1g + 10h + -10h = 0 + -10h Combine like terms: 10h + -10h = 0 1g + 0 = 0 + -10h 1g = 0 + -10h Remove the zero: 1g = -10h Divide each side by '1'. g = -10h Simplifying g = -10h
| 5p+5q=55 | | 9p=49.5 | | (x-0.15)-85=0.20(85) | | 3x+7=7x-6 | | 4(5p+4)= | | 2x-16=8+x | | 243*x-2*x^3=243 | | 9y-6y-11+6= | | 4c+3=84 | | 6c+2=126 | | 2x^3=375 | | 2x^3-10x^2+6x+1=0 | | 5x+8=-69-6x | | 8x=180-10x | | 7+8x=-21+x | | m^3-6m^2+18.5=0 | | 2.5y=4 | | 36sinx=3 | | 2y/=4 | | 9y+6=12 | | (X-8)*(7-sinx)+7-sinx=0 | | 64+28= | | 2n+3k=21 | | 16+16+16+16= | | 93=7x-3 | | 16=3(4x+2)-2 | | 108-24= | | 8x+6=2x-30 | | 6m+3=33 | | 9x-8=5x+5 | | 0.5*n(n-3)=54 | | -3x-17=-2 |